Temperature denpendent microwave absorption properties of SrFe12O19 in X-band - Li, Xiling; Qiao, Liang; Shi, Huigang; Chai, Guozhi; Wang, Tao; Wang, Jianbo (Frontiers in Materials, 2022)
Researchers are currently focusing on the electromagnetic and microwave absorption properties of SrFe12O19 hexaferrites. The high-temperature absorption (more than 573 K) is highly demanded in various including the military, national defense, aviation, and other fields. SrFe12O19 has good thermal stability at high temperature, and it has large coercivity, which also determines that it has good stability in magnetic properties and is not easy to be affected by the environment. Thus, it is necessary to explore the magnetic characteristics of SrFe12O19 hexaferrites at high temperatures. SrFe12O19 hexaferrites were fabricated by the molten salt method and their microstructure, high-temperature electromagnetic properties, and microwave properties were investigated in detail. The complex permeability and permittivity of SrFe12O19 were measured at varying temperatures (293-673 K) in the X band. While the real parts of permittivity and permeability increased with the increasing temperature, the imaginary parts of permittivity and permeability did not change significantly with increasing temperature. The calculated absorption properties displayed that as temperature increased from 293K to 623K, the frequency of the RL peaks moved to a low-frequency direction, and the sample's minimum value of RL could be smaller than -10dB across the whole X band. The results indicate that SrFe12O19 particles have better absorption properties and can be used in high-temperature environments. These particles can be possibly used in many particular fields.